2014
DOI: 10.3892/ol.2014.2746
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-214 functions as a tumor suppressor in human colon cancer via the suppression of ADP-ribosylation factor-like protein 2

Abstract: microRNAs (miRNAs/miRs) are a conserved class of endogenous, short non-coding RNAs that post-transcriptionally regulate the expression of genes involved in diverse cellular processes. miR-214 has been reported to be associated with several cancers, including human colon cancer. However, the function of miR-214 in colon cancer development is poorly understood. In the current study, miR-214 was demonstrated to be downregulated in colon cancer tissues compared with healthy colon tissues. Functional studies showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 26 publications
2
35
0
Order By: Relevance
“…Ectopic overexpression of miR‐214 inhibits cell proliferation and migration of human colon cancer cells. These results are similar to other findings in colon cancer (19, 44, 45). The underlying mechanism of miR‐214 in the progression of colon cancer remains to be clarified.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Ectopic overexpression of miR‐214 inhibits cell proliferation and migration of human colon cancer cells. These results are similar to other findings in colon cancer (19, 44, 45). The underlying mechanism of miR‐214 in the progression of colon cancer remains to be clarified.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, miR‐214 was reported to function as a tumor suppressor in colon cancer (11, 44, 45). miR‐214 inhibits colon cancer proliferation and migration via the suppression of ARL2 (44) and HMGA1 (45). miR‐214/ MED19 axis suppresses tumor growth and metastasis in human CRC (11).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported that miR-499 could inhibit the dephosphorylation of calcineurin-induced Drp1 protein, reduce the accumulation of Drp1 in the mitochondria and inhibit the activation of Drp1-induced mitochondrial fission, in order to keep the cardiomyocytes from apoptosis [29] . According to Targetscan bioinformatic websites [30,31] , it's predicted that miR-208a could be complementarily paired with 3 0 UTR region of calcineurin mRNA, which indicated that miR-208a might also inhibit the calcineurin, inhibit the activation of mitochondrial apoptosis pathway, and thus inhibit the apoptosis. The focus of our further study would be seeking the target gene of miR-208a and the determination whether miR-208a actually inhibits the apoptosis by acting on such target gene.…”
Section: Discussionmentioning
confidence: 99%
“…It has been consistently reported to be deregulated in human cervical (CaCx) and colorectal cancers (CRC) and is associated with suppression of tumour growth and metastasis. A few oncogenic targets like GALNT7 , Bcl2l2 , and TFAM in CaCx and FGF‐1 and ARL2 in CRC have been identified. Many of these targets are suggested to be crucial to promotion of growth, epithelial‐to‐mesenchymal transition (EMT), and metastasis, but the identification of a target that could equally be a hub of deregulated signalling as miR‐214 would open up avenues to contemplate a novel, multidirectional approach to designing therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%